(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This study examines the historical and functional development of the International Monetary Fund (IMF) and its approach to global financial crises and achieving monetary stability from its inception to the present day, starting with the crises of the 1990s in Mexico and southeast Asia and culminating in the global financial crisis. It highlights the most important measures the IMF has taken to mitigate these crisis, including financial assistance, technical advice, and structural reforms, while also presenting these reforms and their effectiveness in achieving stability in the international monetary system. The study clarifies the strengths and weaknesses of the IMF by presenting the advantages and disadvantages of its policies in addressing global monetary and financial crises, The study used analytical method to examine and analyze the policies followed by the International Monetary Fund in dealing with global financial crises, The comparative method was also used by comparing the different strategies followed by the Fund in each of the countries that it helped to emerge from their financial crises, The research concludes that a greater role should be given to struggling developing countries, taking into account the political and social circumstances of each country before implementing IMF support programs.